Effects Of Mechanical Stirring And Short Heat Treatment On Thixoformed Of Carbon Nanotube Aluminium Alloy Composite - Hashim, Hanizam; Salleh, Mohd Shukor; Omar, M.Z.; Sulong, A.B. (Elsevier B.V., 2019)
The present work aimed to determine the effects of thixoforming and short T6 heat treatment processes on the microstructure and mechanical properties of thixoformed A356 alloy reinforced with 0.5 wt% multi-walled carbon nanotube (A356-MWCNT). The semisolid composite feedstock was produced by a mechanical stirring route followed by thixoforming, and finally, it was heat treated with a shorter solution treatment and artificial ageing hours. A premix of 0.5 wt% magnesium (Mg) as wettability agent and MWCNT was injected into molten A356 alloy at 650 °C. Mixing and stirring were performed by a using three-blade impeller at 500 rpm for 10 min, and the mixture was poured into a preheated mould. Microstructure studies show the mechanical stirring effects on the transformation of dendritic arms to mostly globular and rosette structures of α-Al. The formations of more spheroidised structure of eutectic silicon (Si) were predominant after the heat treatment, thereby revealing the effectiveness of shorter T6 heat treatment. Results of field emission scanning electron microscopy images showed uniform distribution and pull-out structures of MWCNT throughout the matrix, thereby justifying the effective load transfer and wettability between reinforcement and alloy matrix. Subsequently, the mechanical properties of the composite shown significant improvements after each stage. The yield strength (YS), ultimate tensile strength (UTS) and elongation to fracture of cast A356 alloy increased from 115 MPa, 132.9 MPa and 1.8% to 135 MPa, 178.3 MPa and 3.1% respectively, in the A356-MWCNT. Consequently, these properties were further improved to 180 MPa, 255.8 MPa and 5.7% after the thixoforming process. The highest attainment of yield strength (YS), ultimate tensile strength (UTS) and elongation to fracture after short T6 of A356-MWCNT were 215 MPa, 277.0 MPa and 7.6%, respectively. The hardness of the samples was improved from 59.5 HV in as-cast alloy to 106.4 HV in thixoformed short T6 A356-MWCNT.